2014
DOI: 10.1089/cap.2014.0008
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Prior Authorization Policies on Medicaid-Enrolled Children's Use of Antipsychotic Medications: Evidence from Two Mid-Atlantic States

Abstract: Prior authorization policies had a modest but statistically significant effect on antipsychotic use in 6-12 year old children, but had no impact in younger children. Future research is needed to understand the utilization and clinical effects of prior authorization and other policies and interventions designed to influence antipsychotic use in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 53 publications
2
29
0
Order By: Relevance
“…This is consistent with the direction of reported outcomes of one other state's antipsychotic prior authorization program during a similar time period; however, the degree of change in antipsychotic prescribing in Washington was more pronounced (Stein et al. ). The 49 percent reduction in the child Medicaid antipsychotic utilization prevalence seen in Washington State following implantation of these consultation programs represents a dramatic change in statewide treatment habits.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This is consistent with the direction of reported outcomes of one other state's antipsychotic prior authorization program during a similar time period; however, the degree of change in antipsychotic prescribing in Washington was more pronounced (Stein et al. ). The 49 percent reduction in the child Medicaid antipsychotic utilization prevalence seen in Washington State following implantation of these consultation programs represents a dramatic change in statewide treatment habits.…”
Section: Discussionsupporting
confidence: 80%
“…The most recently available reports indicate this rising trend of child antipsychotic use has been stabilizing, but not falling (Stein et al. ; Olfson, Druss, and Marcus ). Prevalence of child antipsychotic use have been far from uniform in different demographic groups, in that children with Medicaid coverage have been twice as likely to receive antipsychotics as those with private insurance, and those in foster care have even higher prescription prevalence (Zito et al.…”
mentioning
confidence: 99%
“…The prior authorization study examined the effect of the prior authorization policy on the proportion of Medicaid-enrolled children on antipsychotic medications in PA using a triple-difference strategy including differences between PA and NY, where there was no prior authorization policy; time periods (before and after the introduction of the prior authorization policy in PA), and differences in antidepressant prescribing rates over the same time periods (to control for secular trends in psychotropic prescribing) (Stein et al 2014a). …”
Section: Methodsmentioning
confidence: 99%
“…Analyses demonstrated that claims data on prior psychiatric hospitalizations can identify Medicaid-enrollees disengaged from treatment (Smith et al 2014; populations at higher risk of not re-engaging in treatment (Smith et al 2014), and populations at unusual risk of continued frequent hospitalizations (Stein et al 2014a, b). Further, as few as 4 months of recent claims data are sufficient for this purpose.…”
Section: Project Overviewsmentioning
confidence: 99%
“…A recent study in a mid‐Atlantic state with a peer review program (State A) for pediatric antipsychotic (ATP) review used an abutting state without such review (State B) for comparison (Stein et al. ). Across 3+years, in a complex “triple difference”‐interrupted time series analysis, the analytic method accounted for differences between states, time periods, and rates of antidepressant use.…”
Section: Progress In Other State Programsmentioning
confidence: 99%